2019
DOI: 10.5723/kjcs.2019.40.4.165
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Helicopter Parenting and Depression Among Korean University Students: The Mediating Effect of Assertiveness

Abstract: Objectives: This study aimed to investigate the mediating effect of assertiveness in the relationship between perceived helicopter parenting and depression among university students. Methods: The participants of this study were 609 students (272 males and 337 females) who were enrolled in 25 universities located in Seoul and Gyung-gi province in Korea. The research variables were measured using the Center for Epidemiological Studies-Depression Scale (CES-D), Helicopter Parenting Scale (HPS), and Rathus Asserti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…LeMoyne and Buchanan [34] reported that helicopter parenting could be a factor that hinders children's learning and competitiveness. Several previous studies have emphasized that undergraduate students raised by helicopter parents may have low self-esteem or self-efficacy due to excessive parental control and bondage [20][21][22]. In addition, previous studies have also reported that the parenting behavior of helicopter parents is related to academic burnout and negatively affects the academic achievement of undergraduate students [6,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LeMoyne and Buchanan [34] reported that helicopter parenting could be a factor that hinders children's learning and competitiveness. Several previous studies have emphasized that undergraduate students raised by helicopter parents may have low self-esteem or self-efficacy due to excessive parental control and bondage [20][21][22]. In addition, previous studies have also reported that the parenting behavior of helicopter parents is related to academic burnout and negatively affects the academic achievement of undergraduate students [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, with interest in helicopter parenting growing in various academic fields, several studies have examined the relationship between helicopter parenting and depression in undergraduate students [4,19,20], the relationship between helicopter parenting and university students' academic achievement [6,7], and helicopter parenting attributes [21]. Studies of nursing students have been conducted to conceptually analyze helicopter parenting [9], develop a helicopter parenting scale [22], and examine the relationship between helicopter parenting and learning competence of nursing students [23].…”
Section: Introductionmentioning
confidence: 99%
“…With this circumstance, the literature on helicopter parenting has been mainly conducted to examine the effect of psycho-emotional factors on undergraduate students (Park and Jin, 2021). For example, based on previous studies conducted in Western countries, studies on the association between helicopter parenting and depression have been conducted in Korea (Kim and Park, 2019). In addition, college students who perceived higher levels of helicopter parenting tended to have a lower number of children in the future (Yoo, 2014).…”
Section: Helicopter Parenting Studies In Koreamentioning
confidence: 99%
“…. 그러나 사회적 환경과 자녀 수의 급 감으로 인해 가족 구성의 변화가 이루어지고 있으며, 그 결과로 자 녀에게 노력과 애정을 쏟는 부모가 증가하고 자녀에 대한 관여와 개입이 지나치게 높아지고 있는 현상이 나타나고 있다 (Au & Lee, 2018;Kim & Park, 2019;Mau, 2000;Sovet & Metz, 2014). 최근 연구들에 따르면 귀인은 학업 성취 분야를 넘어서 진로 분야까지 영역이 확대되고 있다 (Son, 2006).…”
unclassified